2017
DOI: 10.3892/ol.2017.7601
|View full text |Cite
|
Sign up to set email alerts
|

Association between clinicopathological factors and postoperative radiotherapy in patients with completely resected pathological N2 non-small cell lung cancer

Abstract: Abstract. The function of postoperative radiotherapy (PORT) in patients with completely resected pathologically N2 (pN2) non-small cell lung cancer (NSCLC) remains controversial due to a lack of prospective studies. The present study aimed to evaluate the efficacy of PORT in completely resected pN2 NSCLC when using modern radiation techniques, and to determine the associations between clinicopathological factors and PORT and survival rates. Following patient selection, 246 out of 269 consecutive patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
5
1
Order By: Relevance
“…This information helps to determine the indications for adjuvant chemotherapy, which reportedly has therapeutic effects (28). As previously reported, N2 is a prognostic factor for survival in patients with lung cancer who have undergone radical resection (29). The pathological N factor was one of the clinical factors associated with DFS in left upper lobe lung cancer in this study.…”
Section: Discussionsupporting
confidence: 77%
“…This information helps to determine the indications for adjuvant chemotherapy, which reportedly has therapeutic effects (28). As previously reported, N2 is a prognostic factor for survival in patients with lung cancer who have undergone radical resection (29). The pathological N factor was one of the clinical factors associated with DFS in left upper lobe lung cancer in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, a number of studies investigated the efficacy of PORT for pIIIA-N2 NSCLC according to the N2 metastasis status. Several retrospective studies 14, 18, 19, including two population-based studies 16,17, demonstrated the benefit of PORT in terms of improving OS for patients with multiple N2 metastases or multiple N2 station involvement, but not for patients with single N2 station involvement. However, the subgroup analysis of a recent randomized phase II study 20 revealed that postoperative chemotherapy (POCT) alone was favored compared with POCRT in patients with multiple N2 station involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, with the widespread use of X-ray linear accelerators and the emergence of technologies such as 3-dimensional conformal rt and intensity-modulated rt, the conformity index of the target volume, the dose distribution, and the organs at risk doses have all been improved, and radiation-related toxicity is also well controlled 6 . As a result, port has been validated in several studies to improve survival for patients classified pN2 5,7,8 . In the present study, port was implemented based on modern rt technologies (40 patients received 3-dimensional conformal rt, and 183 received intensity-modulated rt).…”
Section: Discussionmentioning
confidence: 99%
“…However, the meta-analysis was also disputable because of its inclusion of outdated studies, older radiotherapy (rt) techniques, and incomplete surgical information. Subsequently, some studies verified that, with modern rt techniques, port is sufficiently safe 6 and can improve the postoperative survival of patients with pN2 nsclc 5,7,8 . However, some scholars have held the opposite opinion 9,10 , making it crucially important to screen for patients who might benefit from port.…”
Section: Introductionmentioning
confidence: 99%